Climate Change - It2019;s Impact on our Behaviour and why we Need to Change it Now (Global Journal of Medical Research, 2021)
Our days today begin with news either of the varying statistics of the COVID-19 cases tragedies of prejudicial discrimination follies of policy-makers horrifying terrorist attacks and more dreary information that are not only grave but also petrifying Amongst these the global concern that touches all living creatures is the news of our weary planet COP26 or the UN Climate Summit 2021 is going to take place for 2 weeks from the 31st of October to the 12th of November in Glasgow and it has been the matter of the moment for the past few weeks The cause is unsurprising and is frankly long overdue Climate change is an upsetting phenomenon both for our planet and its inhabitants Our persistent activities of pleasure for personal gain at the expense of Mother Earth can no longer be put up with Not by our planet not by the future generations Their survival and ours solely depends on us fixing our current ways While the prospect is daunting fear cannot be our barrier Our present psychological mindsets need a jolt It is now essential that we step past the fear of change to make the change possible for we are hanging by a thread at the end of the rope with a fire beneath The consequences are cataclysmic and we are our only hope
Keywords: climate change; earth matters; climate anxiety